Answer to Question #221128 in Differential Equations for Shivam

Question #221128

p²+q²=4


1
Expert's answer
2021-08-30T05:25:33-0400

"\\frac {dx}{-fp} =\\frac {dy}{-fq} =\\frac {dz}{(-p*fp-q*fq)} =\\frac {dp}{(fx+x*fz)} =\\frac {dq}{(fy+y*fz)}\\\\\nSince,\\space\\frac {dq}{(fy+y*fz)}=\\frac {dq}{0}\\\\\n=>q=a\\\\\n\\text{from the given pde, we get}\\\\\n=>p=\\pm \\sqrt{4-a^2}\\\\\nThen,\\\\\ndz=pdx+qdy\\\\\ndz=\\pm\\sqrt{4-a^2}dx+ady\\\\\n\\text{Integrating both side, we get}\\\\\nz=\\pm\\sqrt{4-a^2}x+ay+c\\\\\n\\text{NOTE:- We can take either p is constant from} \\frac {dp}{(fx+x*fz)}=\\frac {dp}{0} \\text{or qas a constant.}"


Need a fast expert's response?

Submit order

and get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

Comments

No comments. Be the first!

Leave a comment